PARENTS' PERCEPTION OF HABITS AND KNOWLEDGE LEVEL OF ORAL HEALTH IN CHILDREN WITH SPECIAL NEEDS - Sukma, Novita; Soerachman, Badi (Fakultas Kedokteran Gigi Unjani, 2024)
Children with special needs are defined as physical, mental, social, and emotional limitations that significantly influence growth and development. The restrictions affect oral health, so the parents' role is significant in improving oral health. This study aims to determine the perception of habits and the level of parents' knowledge regarding dental and oral health maintenance in children with special needs. The research used was a cross-sectional method using a questionnaire. The research sample consisted of parents of students from (Sekolah Luar Biasa (SLB) Citereup Cimahi, with a total sample of up to 91 children aged 6 - 18 years. Characteristics of students include mentally retarded, physically disabled, visual impairment, hearing impairment, autism and types with other disorders. The results showed that parents' perceptions of maintaining oral health are poor because some parents are still ignorant of the discipline of maintaining dental hygiene; on the contrary, more than 55 % of the level of knowledge was exemplary. The research results concluded that parents have good knowledge about oral health, but many parents still neglect to maintain oral health. DOI : 10.54052/jhds.v3n3.p291-302